Relationship between Degree of Exercise Participation and Active Aging among Older Adults - Yung-Tzung Chang; Chen-Wei Yu; Cheng-Min Chao; Rueg-Juen Chen (Advances in Public Health)
Government departments and scholars have focused on promoting health care for older adults in response to population aging and the annual increase in the number of older adults. Old age does not necessarily involve rapid health decline, fragility, or senility. Therefore, active aging among older adults has become a major consideration worldwide. The effect of exercise participation and social support on active aging warrants investigation. This study proposes a conceptual model for understanding the effects of exercise participation and social support on active aging among older adults. Exercise participation, social support, and health literacy were integrated to hypothesize a theoretical model of active aging among older adults. Furthermore, the moderating role of health literacy in the relationship between exercise participation, social support, and active aging was analyzed. Questionnaires were administered to respondents from Northern Taiwan during face-to-face interviews. Of the 1,800 distributed questionnaires, 1,586 completed questionnaires were received (response rate = 88.1%). The data collected were analyzed using structural equation modeling. The results indicated that exercise participation (β = 0.163, p=0.000), social support (β = 0.384, p=0.000), and health literacy (β = 0.360, p=0.000) had significant positive effects on active aging. Health literacy did not moderate the effects of exercise participation and social support on active aging among older adults (β = −0.054, p=0.197 and 0.061, p=0.066). The current results confirm that social support has a considerable effect on active aging, which could be used as a reference for future proposals targeted at relevant institutions and older adults.